Controversies in the contemporary world - Fabris, Adriano, 1958-; Scarafile, Giovanni (Controversies, 2019)
"Inspired by Marcelo Dascal's theory of controversies, this volume includes studies in the theory of controversies, studies of the history of controversy forms and their evolution, case-studies of particular historical and current controversies. The purpose of this volume is to identify a taxonomy of controversies and also to sense a line of development for the phenomenon itself of controversies. At the same time, we want to ask ourselves about the impact and the spread of controversies in the contemporary world, eminently intended as a heuristic element facilitating knowledge. For all these reasons, the fundamental aim of the volume is to provide the reader with a selection of current theoretical and practical perspectives on controversies, and to offer a broad picture of the complex range of definitions, meanings and practices connected to it"--